PENGEMBANGAN KARIR TENAGA PENDIDIKAN DI SEKOLAH MENENGAH ATAS SWASTA LABORATORIUM PERCONTOHAN UPI - Zaini Hafidh; Yayah Rahyasih; Tia Oktaviani (INCARE, International Journal of Educational Resources, 2022)
This research aims to find out the career development that exists at UPI Laboratory School High School. Career development in Human Resource Management (MSDM) is very important in improving and increasing the effectiveness of the implementation of existing work in a school institution so that it can realize the goals that have been set following the school's vision and mission. In Human Resource Management at present time it is carried out by developing Information Technology (IT), which is an opportunity and a challenge in achieving goals that have competitiveness in creating jobs. This study uses a type of qualitative research with a case study approach. Data collection techniques were carried out through interviews, observation, and document studies. Data analysis in the form of unitization of data, categorization, and interpretation of data as well as a data validation test. This career development can have a positive impact on the change process by carrying out a series of positions, jobs, and positions. Schools provide facilities in development to increase the knowledge and ability of an employee to be more effective. Strong Human Resources can give birth to schools with the adaptability and capacity to update the system. In this case, of course, it must aim to develop an environment that encourages employees to learn and develop better than before.